2021
DOI: 10.3390/s21030887
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring in Chronic Heart Failure Patients: Is Non-Invasive Remote Monitoring the Way to Go?

Abstract: Heart failure (HF) is a major health care issue, and the incidence of HF is only expected to grow further. Due to the frequent hospitalizations, HF places a major burden on the available hospital and healthcare resources. In the future, HF care should not only be organized solely at the clinical ward and outpatient clinics, but remote monitoring strategies are urgently needed to guide, monitor, and treat chronic HF patients remotely from their homes as well. The intuitiveness and relatively low costs of non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 81 publications
0
18
0
4
Order By: Relevance
“…ХСН -одна из основных причин госпитализации и преждевременной смерти больных ССЗ. Своевременное выявление ухудшения состояния у таких пациентов может привести к уменьшению числа их госпитализаций и улучшению прогноза заболевания [13]. Применение дистанционного наблюдения позволяет повысить информированность и приверженность лечению среди больных ССЗ, а также вовремя выявить необходимость в оказании им медицинской помощи, но данная методика должна быть адаптирована и внедрена в имеющуюся систему здравоохранения [14].…”
Section: персональные устройства для удаленного мониторинга легочной гемодинамикиunclassified
See 1 more Smart Citation
“…ХСН -одна из основных причин госпитализации и преждевременной смерти больных ССЗ. Своевременное выявление ухудшения состояния у таких пациентов может привести к уменьшению числа их госпитализаций и улучшению прогноза заболевания [13]. Применение дистанционного наблюдения позволяет повысить информированность и приверженность лечению среди больных ССЗ, а также вовремя выявить необходимость в оказании им медицинской помощи, но данная методика должна быть адаптирована и внедрена в имеющуюся систему здравоохранения [14].…”
Section: персональные устройства для удаленного мониторинга легочной гемодинамикиunclassified
“…Различные подходы к удаленному наблюдению за пациентами с ХСН включают регулярные телефонные опросы (структурированная поддержка по телефону), контроль фи зической активности, телемониторинг ЭКГ, веса, диуреза, АД, сатурации и некоторых других показателей, а также применение имплантируемых антиаритмических устройствмониторинг с использованием имплантируемых кардиовертеров-дефибрилляторов (ИКД), сердечную ресинхронизирующую терапию (СРТ) [13].…”
Section: персональные устройства для удаленного мониторинга легочной гемодинамикиunclassified
“…The recent COVID-19 pandemic and the associated transition of patient care outside the hospital have boosted the development of systems for the remote monitoring of patient vitals signs [1][2][3], a task that has also been favored by the advancement of wearable technologies [4][5][6][7][8][9] and the Internet of Things (IoT). These two technologies have contributed to the widespread adoption of smart healthcare solutions (soft transducer), deployed either at hospitals or at home [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The small number of participants, the retrospective observational nature of the study, and the absence of simultaneous control participants make these results only hypothesis generating results, but they do run in line with current literature. Although randomized controlled trials (RCTs) in the last decade showed divergent results regarding the efficacy of telemedicine in heart failure, 2 systematic reviews showed a reduction in hospitalizations and mortality among this population. A Cochrane systematic review in 2015, including only RCTs, evaluated the use of structured telephone support or non-invasive home telemonitoring compared to standard practice for people with heart failure.…”
mentioning
confidence: 99%
“…O uso de tecnologias de telecomunicação traz vantagens possíveis em relação à assistência presencial, superando barreiras organizacionais e geográficas. Entretanto, resultados divergentes em ensaios randomizados avaliando a eficácia da telemedicina na redução de hospitalizações e mortalidade por insuficiência cardíaca 2 desencorajaram o uso rotineiro de recursos digitais na prática clínica até a pandemia da COVID-19.…”
unclassified